“Dyeing Commodities whether in Roote or floure”: Reconstructing Aboriginal Dye Techniques from Documentary and Museum Sources - Bohr, Roland; Lindsay, Anne (Material Culture Review, 2009)
This paper considers the differences found in various documentary sources purporting to describe Aboriginal quill dyeing techniques. The authors identified a number of recipes for quill dyeing that were collected by fur traders, explorers and ethnologists. They then attempted to reproduce the recipes. Finally, they worked the dyed quills into characteristic patterns and compared the results to existing artifacts from museum collections. The results of this research suggest that the amount of detail, accuracy and reproducibility in recipes varied widely between sources. The authors suggest that the reasons why various authors collected these dye recipes may explain, at least in part, the differences in recipes, but that, also, connections to communities and other factors must be considered when discussing the reproducibility of dye recipes. This research is preliminary. Further avenues of research are suggested. RésuméCet article examine les différences découvertes dans diverses sources documentaires décrivant les techniques autochtones de teinture de piquants de porc-épic. Leurs auteurs mentionnaient un certain nombre de recettes recueillies par des traiteurs de fourrures, des explorateurs et des ethnologues. Ils essayaient par la suite de reproduire ces recettes, d’agencer les piquants de porc-épic en motifs caractéristiques et de comparer leurs résultats aux artefacts présents dans les collections muséales. Les résultats de notre recherche montrent que les détails, l’exactitude et la reproductibilité des recettes variaient considérablement entre les différentes sources. Nous suggérons que c’est la diversité des raisons pour lesquelles les différents auteurs ont collecté ces recettes qui peut expliquer, du moins en partie, les différences entre ces dernières, mais qu’il faut également prendre en considération les liens avec les communautés et d’autres facteurs pour examiner la reproductibilité de ces recettes tinctoriales. Cette recherche n’en est qu’à ses débuts et d’autres pistes de recherche seront avancées ici